Diversity of squat lobsters on coral reefs in Guam, Mariana Islands, with the description of two new species and notes on their natural history - Paula C. Rodríguez-Flores; Héctor Torrado; David Combosch; Gonzalo Giribet (Marine Biodiversity, 2024)

Consensus Guidelines for Advancing Coral Holobiont Genome and Specimen Voucher Deposition - Christian R. Voolstra; Kate M. Quigley; Sarah W. Davies; John Everett Parkinson; Raquel S. Peixoto; Manuel Aranda; Andrew C. Baker; Adam R. Barno; Daniel J. Barshis; Francesca Benzoni; Victor Bonito; David G. Bourne; et al. (Frontiers in Marine Science, 2021)
Coral research is being ushered into the genomic era. To fully capitalize on the potential discoveries from this genomic revolution, the rapidly increasing number of high-quality genomes requires effective pairing with rigorous taxonomic characterizations of specimens and the contextualization of their ecological relevance. However, to date there is no formal framework that genomicists, taxonomists, and coral scientists can collectively use to systematically acquire and link these data. Spurred by the recently announced “Coral symbiosis sensitivity to environmental change hub” under the “Aquatic Symbiosis Genomics Project” - a collaboration between the Wellcome Sanger Institute and the Gordon and Betty Moore Foundation to generate gold-standard genome sequences for coral animal hosts and their associated Symbiodiniaceae microalgae (among the sequencing of many other symbiotic aquatic species) - we outline consensus guidelines to reconcile different types of data. The metaorganism nature of the coral holobiont provides a particular challenge in this context and is a key factor to consider for developing a framework to consolidate genomic, taxonomic, and ecological (meta)data. Ideally, genomic data should be accompanied by taxonomic references, i.e., skeletal vouchers as formal morphological references for corals and strain specimens in the case of microalgal and bacterial symbionts (cultured isolates). However, exhaustive taxonomic characterization of all coral holobiont member species is currently not feasible simply because we do not have a comprehensive understanding of all the organisms that constitute the coral holobiont. Nevertheless, guidelines on minimal, recommended, and ideal-case descriptions for the major coral holobiont constituents (coral animal, Symbiodiniaceae microalgae, and prokaryotes) will undoubtedly help in future referencing and will facilitate comparative studies. We hope that the guidelines outlined here, which we will adhere to as part of the Aquatic Symbiosis Genomics Project sub-hub focused on coral symbioses, will be useful to a broader community and their implementation will facilitate cross- and meta-data comparisons and analyses.

Differential gene expression during substrate probing in larvae of the Caribbean coral Porites astreoides - Nia S. Walker; Rosa Fernández; Jennifer M. Sneed; Valerie J. Paul; Gonzalo Giribet; David J. Combosch (Molecular Ecology, 2019)
The transition from larva to adult is a critical step in the life history strategy of most marine animals. However, the genetic basis of this life history change remains poorly understood in many taxa, including most coral species. Recent evidence suggests that coral planula larvae undergo significant changes at the physiological and molecular levels throughout the development. To investigate this, we characterized differential gene expression (DGE) during the transition from planula to adult polyp in the abundant Caribbean reef‐building coral Porites astreoides, that is from nonprobing to actively substrate‐probing larva, a stage required for colony initiation. This period is crucial for the coral, because it demonstrates preparedness to locate appropriate substrata for settlement based on vital environmental cues. Through RNA‐Seq, we identified 860 differentially expressed holobiont genes between probing and nonprobing larvae ( p ≤ .01), the majority of which were upregulated in probing larvae. Surprisingly, differentially expressed genes of endosymbiotic dinoflagellate origin greatly outnumbered coral genes, compared with a nearly 1:1 ratio of coral‐to‐dinoflagellate gene representation in the holobiont transcriptome. This unanticipated result suggests that dinoflagellate endosymbionts may play a significant role in the transition from nonprobing to probing behaviour in dinoflagellate‐rich larvae. Putative holobiont genes were largely involved in protein and nucleotide binding, metabolism and transport. Genes were also linked to environmental sensing and response and integral signalling pathways. Our results thus provide detailed insight into molecular changes prior to larval settlement and highlight the complex physiological and biochemical changes that occur in early transition stages from pelagic to benthic stages in corals, and perhaps more importantly, in their endosymbionts.

Population substructure and signals of divergent adaptive selection despite admixture in the sponge Dendrilla antarctica from shallow waters surrounding the Antarctic Peninsula - Carlos Leiva; Sergi Taboada; Nathan J. Kenny; David Combosch; Gonzalo Giribet; Thibaut Jombart; Ana Riesgo (Molecular Ecology, 2019)
Antarctic shallow‐water invertebrates are exceptional candidates to study population genetics and evolution, because of their peculiar evolutionary history and adaptation to extreme habitats that expand and retreat with the ice sheets. Among them, sponges are one of the major components, yet population connectivity of none of their many Antarctic species has been studied. To investigate gene flow, local adaptation and resilience to near‐future changes caused by global warming, we sequenced 62 individuals of the sponge Dendrilla antarctica along the Western Antarctic Peninsula (WAP) and the South Shetlands (spanning ~900 km). We obtained information from 577 double digest restriction site‐associated DNA sequencing (ddRADseq)‐derived single nucleotide polymorphism (SNP), using RADseq techniques for the first time with shallow‐water sponges. In contrast to other studies in sponges, our 389 neutral SNPs data set showed high levels of gene flow, with a subtle substructure driven by the circulation system of the studied area. However, the 140 outlier SNPs under positive selection showed signals of population differentiation, separating the central–southern WAP from the Bransfield Strait area, indicating a divergent selection process in the study area despite panmixia. Fourteen of these outliers were annotated, being mostly involved in immune and stress responses. We suggest that the main selective pressure on D. antarctica might be the difference in the planktonic communities present in the central–southern WAP compared to the Bransfield Strait area, ultimately depending on sea‐ice control of phytoplankton blooms. Our study unveils an unexpectedly long‐distance larval dispersal exceptional in Porifera, broadening the use of genome‐wide markers within nonmodel Antarctic organisms.

Genomic signatures of evolution in Nautilus —An endangered living fossil - David J. Combosch; Sarah Lemer; Peter D. Ward; Neil H. Landman; Gonzalo Giribet (Molecular Ecology, 2017)
Living fossils are survivors of previously more diverse lineages that originated millions of years ago and persisted with little morphological change. Therefore, living fossils are model organisms to study both long‐term and ongoing adaptation and speciation processes. However, many aspects of living fossil evolution and their persistence in the modern world remain unclear. Here, we investigate three major aspects of the evolutionary history of living fossils: cryptic speciation, population genetics and effective population sizes, using members of the genera Nautilus and Allonautilus as classic examples of true living fossils. For this, we analysed genomewide ddRAD‐Seq data for all six currently recognized nautiloid species throughout their distribution range. Our analyses identified three major allopatric Nautilus clades: a South Pacific clade, subdivided into three subclades with no signs of admixture between them; a Coral Sea clade, consisting of two genetically distinct populations with significant admixture; and a widespread Indo‐Pacific clade, devoid of significant genetic substructure. Within these major clades, we detected five Nautilus groups, which likely correspond to five distinct species. With the exception of Nautilus macromphalus , all previously described species are at odds with genomewide data, testifying to the prevalence of cryptic species among living fossils. Detailed F ST analyses further revealed significant genome‐wide and locus‐specific signatures of selection between species and differentiated populations, which is demonstrated here for the first time in a living fossil. Finally, approximate Bayesian computation ( ABC ) simulations suggest large effective population sizes, which may explain the low levels of population differentiation commonly observed in living fossils.

Interspecific hybridization and restricted trans‐Pacific gene flow in the Tropical Eastern Pacific Pocillopora - DAVID J. COMBOSCH; HECTOR M. GUZMAN; HELMUT SCHUHMACHER; STEVEN V. VOLLMER (Molecular Ecology, 2008)
Coral reefs in the Tropical Eastern Pacific (TEP) are among the most isolated in the world. This isolation has resulted in relatively low species diversity but comparatively high endemism. The dominant reef‐building corals of the TEP are the Pocillopora corals, a ubiquitous Indo‐Pacific genus commonly regarded as inferior reef‐builder. In addition to being the dominant reef‐builders in the TEP, the Pocilloporids have undergone a reproductive shift from internally brooding larvae through most of their Indo‐Pacific range to free‐spawning in the TEP. Using genetic data from the internally transcribed spacer (ITS) regions of the nuclear ribosomal DNA gene cluster, we show here that this apparent reproductive shift coincides with interspecific hybridization among TEP Pocillopora species. We document a pattern of one‐way gene flow into the main TEP reef builder P. damicornis from one or both of its TEP congeners — P. eydouxi and P. elegans . Our data provide preliminary evidence that trans‐Pacific gene flow in P. damicornis between the Central and Eastern Pacific is restricted as well (Φ ST = 0.419, P